2014
DOI: 10.1002/tox.21975
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of puerarin against tetrabromobisphenol a‐induced apoptosis and cardiac developmental toxicity in zebrafish embryo‐larvae

Abstract: Tetrabromobisphenol A (TBBPA), a brominated flame retardant, is detected commonly in aquatic environments, where it is thought to be highly toxic to the development of aquatic life. In this study, zebrafish embryos and larvae were used to investigate the protective effects of puerarin after exposure to TBBPA. Malformation, blood flow disorders, pericardial edema, and spawn coagulation rates increased, whereas survival decreased significantly after exposure to 0.5 and 1.0 mg L(-1) TBBPA. The measured indices of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…There are conflicting reports on whether TBBPA has estrogenic activity in larval zebrafish with one group (Chow et al, 2013) reporting increased vitellogenin (an estrogenic biomarker in zebrafish) expression at high TBBPA concentrations, but another group reporting no estrogenic activity (Song et al, 2014). Many different laboratories (Kalasekar et al, 2014; McCormick et al, 2010; Noyes et al, 2015; Song et al, 2014; Yang et al, 2014) have reported that TBBPA produces malformations and lethality in developing zebrafish in the low micromolar ranges in agreement with our reported POD of 4.6 µM (Table 3). We did not observe changes in behavior after developmental exposure, but we did note marked changes in behavior after acute exposure, which correlates with what has been reported in mammals: TBBPA is, at most, a weak developmental neurotoxicant in mammals (Cope et al, 2015; Eriksson et al, 2001; Lilienthal et al, 2008), but it does appear to produce extensive behavioral changes after an acute exposure in mice (Nakajima et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…There are conflicting reports on whether TBBPA has estrogenic activity in larval zebrafish with one group (Chow et al, 2013) reporting increased vitellogenin (an estrogenic biomarker in zebrafish) expression at high TBBPA concentrations, but another group reporting no estrogenic activity (Song et al, 2014). Many different laboratories (Kalasekar et al, 2014; McCormick et al, 2010; Noyes et al, 2015; Song et al, 2014; Yang et al, 2014) have reported that TBBPA produces malformations and lethality in developing zebrafish in the low micromolar ranges in agreement with our reported POD of 4.6 µM (Table 3). We did not observe changes in behavior after developmental exposure, but we did note marked changes in behavior after acute exposure, which correlates with what has been reported in mammals: TBBPA is, at most, a weak developmental neurotoxicant in mammals (Cope et al, 2015; Eriksson et al, 2001; Lilienthal et al, 2008), but it does appear to produce extensive behavioral changes after an acute exposure in mice (Nakajima et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Decreased number of TUNEL-positive cells evidenced the attenuated apoptosis in puerarin-treated rats. The anti-apoptotic effect of puerarin we observed here is consistent with previous studies which were focused on other diseases [41][42][43] and it may promote the recovery of rats from SCI.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, thioredoxin (redox protein, antioxidant), glutaredoxin (redox enzyme), and protein disulfide isomerase (catalyzes protein folding) suggest that the treatment caused oxidative stress and tissue damage in the eye, which was antagonized by those redox and repair proteins. For both THDCs, induction of oxidative stress and reactive oxygen species formation in fish and rodents has been described before [44,45].…”
Section: Discussionmentioning
confidence: 99%